PENGEMBANGAN MEDIA AUDIO-VISUAL BERBASIS PLOTAGON DAN QUIZ BERBASIS WORDWALL PADA PEMBELAJARAN SKI KELAS VIII DI MTS - Mahrita Mahrita; Eka Dwi Ningsih; Raisa Adilla; Abdul Aziz (JOURNAL SAINS STUDENT RESEARCH, 2024)
In the current era, learning increasingly relies on digital media, which has become an important demand in the education process. Digital media plays a significant role in making it easier for students to understand the subject matter in the classroom, thus increasing the effectiveness and efficiency of learning. This research aims to develop audio-visual learning media based on the plotagon application combined with wordwall-based interactive quizzes. The method used is research and development with the ADDIE model, which has stages including needs analysis, design, development, implementation, and evaluation of learning media. Through learning videos about the progress of science during the Abbasid period and interactive quizzes, students are expected to better understand material that was previously considered abstract. This media is designed to increase students' understanding and participation in learning. With interesting visualizations and the use of technology, this research aims to create a more effective learning atmosphere, so that students can be more focused and motivated. The results of the research are expected to make a positive contribution to the quality of Islamic Cultural History learning as well as increasing student engagement in the classroom.